The global decline of cheetah Acinonyx jubatus and what it means for conservation - Durant, Sarah M; Mitchell, Nicholas; Groom, Rosemary; Pettorelli, Nathalie; Ipavec, Audrey; Jacobson, Andrew P; Woodroffe, Rosie; Böhm, Monika; Hunter, Luke T B; Becker, Matthew S; Broekhuis, Femke; Bashir, Sultana; et al. (Proceedings of the National Academy of Sciences - PNAS, 2017)
Establishing and maintaining protected areas (PAs) are key tools for biodiversity conservation. However, this approach is insufficient for many species, particularly those that are wide-ranging and sparse. The cheetah Acinonyx jubatus exemplifies such a species and faces extreme challenges to its survival. Here, we show that the global population is estimated at ∼7,100 individuals and confined to 9% of its historical distributional range. However, the majority of current range (77%) occurs outside of PAs, where the species faces multiple threats. Scenario modeling shows that, where growth rates are suppressed outside PAs, extinction rates increase rapidly as the proportion of population protected declines. Sensitivity analysis shows that growth rates within PAs have to be high if they are to compensate for declines outside. Susceptibility of cheetah to rapid decline is evidenced by recent rapid contraction in range, supporting an uplisting of the International Union for the Conservation of Nature (IUCN) Red List threat assessment to endangered. Our results are applicable to other protection-reliant species, which may be subject to systematic underestimation of threat when there is insufficient information outside PAs. Ultimately, conserving many of these species necessitates a paradigm shift in conservation toward a holistic approach that incentivizes protection and promotes sustainable human-wildlife coexistence across large multiple-use landscapes.